PENANAMAN NILAI AGAMA DALAM MEMBENTUK SISWA MANDIRI DI SMP RIYADUL MUBTADIN MANDALAWANGI - Didih M Sudi; Hidayat, Ahmad; Kurnaesih, Uun; Budiana, Budiana (Staisman Press, 2023)
The background of this research is that there is a lack of instilling students' character values ​​to apply religious behavior in themselves, especially in learning Islamic religious education. With these problems, the authors identify problems in the form of: (1) the level of awareness of students who are still low in implementing religious behavior, (2) the low learning achievement of students in learning Islamic Religious Education, (3) The application of religious character education which is considered not yet implemented effectively, and (4) various problems related to the character of students who are very worried about the community. This research is a qualitative descriptive study, taking the background of Riyadul Mubtadin Mandalawangi Middle School. Data collection was carried out by means of observation, interviews, questionnaires, and documentation. The data analysis consists of data collection, data reduction, data presentation, and drawing conclusions and verification. The results of this study indicate that Islamic Islamic education learning activities in forming the religious character of students there are three stages, namely lesson planning, learning implementation, and evaluation. As for the forms of character that are instilled in students in PAI subjects, namely, religious, disciplined, honest, hard work, tolerance, creative, independent, democratic, curiosity, national spirit, love of the motherland, respect for achievement, friendly communication, love peace , fond of reading, environmental care, social care, and responsibility. Where all these character values ​​must be included in every learning process, especially in Islamic Religious Education subjects. As for achieving the inculcation of students' religious character values ​​in learning Islamic religious education, several methods are used in the form of habituation methods, advice methods, giving attention methods, and punishment methods.